Examining the transnational preventive healthcare utilisation of a group of Eastern European migrants living full-time in another European state. Issue 4 (April 2022) - Kelleher, Dan; Doherty, Edel; O'Neill, Ciaran
Highlights: Migrants have lower use of preventive healthcare in Europe. Polish migrants have less use of preventive healthcare in Ireland. Polish migrants substitute blood or urine test uptake in Ireland for Poland. Transnational ties can determine the preventive care utilisation of migrants in Europe. Abstract: Migrants in Europe are shown to have consistently lower uptake of preventive healthcare compared to European host populations. This paper examines how the transnational preventive care use of Eastern European migrants in their country of origin may be associated with preventive care uptake in their European host country. Preventive care use data in Ireland was collected on 119 Polish migrants and 123 native Irish from June 2018 to September 2019. Preventive care use data was also collected on the Polish migrant group in Poland during the same period. Preventive care use was captured by examining general practitioner visits, blood or urine test uptake, and cancer screening uptake. Probit models were first estimated to examine whether the Polish migrants were more or less likely to have used each service in Ireland than the native Irish. Second, three bivariate probit models were estimated to examine the use of each service by the Polish migrants only in Ireland and Poland as the two dependant variables. The Polish migrants are less likely to have GP visits, blood or urine test uptake, and cancer screening uptake in Ireland compared to the native Irish. The Polish migrants from this study are also shown to potentially substitute blood or urine test uptake in Ireland for uptake in Poland. Transnational ties can determine the preventive care utilisation of migrants in Europe.